2015
DOI: 10.1093/jac/dku563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of provider and urgent care density across different socioeconomic strata on outpatient antibiotic prescribing in the USA

Abstract: In areas with higher poverty rates, access to providers drives the prescribing rate. However, in wealthier areas, where access is less of a problem, a higher density of providers and clinics increases the prescribing rate, potentially due to competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…It is uncertain whether states with higher antibiotic prescribing rates have more inclusive criteria for a septicemia diagnosis (boosting the association between antibiotic prescribing rates and septicemia hospitalization rates), or vice versa. For example, California has relatively low antibiotic prescribing rates [52] and apparently more inclusive criteria for a septicemia/sepsis diagnosis that translate into lower case fatality rates for such hospitalizations compared to the national average, e.g. [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain whether states with higher antibiotic prescribing rates have more inclusive criteria for a septicemia diagnosis (boosting the association between antibiotic prescribing rates and septicemia hospitalization rates), or vice versa. For example, California has relatively low antibiotic prescribing rates [52] and apparently more inclusive criteria for a septicemia/sepsis diagnosis that translate into lower case fatality rates for such hospitalizations compared to the national average, e.g. [53].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other work has shown that where provider density is higher, inappropriate antimicrobial prescribing is higher. 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…In Europe, these geographical variations have been attributed to socioeconomic (eg, financial wellbeing and access to health insurance), sociodemographic (eg, urbanization), and cultural (eg, educational level, prescribing norms, and patient demands) factors. 8,9 Furthermore, there is evidence that antibiotic prescription rates vary considerably according to age and sex. 5,10 In Italy, where the consumption of systemic antibiotics is higher than the European average, 2,11,12 antibiotic prescription rates vary among different regions, 5,13,14 showing a higher antibiotic consumption in Southern Italy.…”
Section: Introductionmentioning
confidence: 99%